PENGARUH SERTIFIKASI DIRI (SELF-CERTIFICATION) TERHADAP SLACK ANGGARAN: PERAN PENGENDALIAN INFORMAL DALAM MEMITIGASI PERILAKU OPORTUNIS: PENDEKATAN EKSPERIMEN - Yandra, Fachmi Pachlevi; Kusuma, Dheni Indra (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2019)
ABSTRACT Budget participation raises the problem of opportunistic behavior in the form of budgetary slack. Budget slack occurs when employees try to use information to overestimate the estimated resources needed or reduce the estimated income that can be achieved to make it easier for them to achieve cost efficiency and performance targets, so that they get better performance evaluation scores. In terms of accounting, organizations try to prevent or reduce slack behavior because it has consequences for the loss of opportunities for profits or increased costs. This study aims to conduct laboratory experiments to test the role of self-certification as a variable capable of mitigating budget slack behavior. The participants who will be used in this study are S1 and S2 students of YKPN College of Economics, Yogyakarta. The reason for choosing students as participants is because the assignments given in this experiment only require individual general cognitive abilities, not special abilities that require judgment and individual work experience. Research data collection was carried out using a 1 x 2 experimental design between subjects. The experiment will be carried out using a computer-assisted program. The assignment given was the assignment of